Improvement and Unification of Input Images for Photogrammetric Reconstruction - Skabek, Krzysztof; Łabędź, Piotr; Ozimek, Pawel (Computer Assisted Methods in Engineering and Science; Vol 26 No 3-4 (2019), 2020)
In this paper, we compare techniques for 3D reconstruction from images. We focus on the pre-processing step of reconstruction: improving the input images. Several image processing algorithms are selected and tested. The main goal is to improve the quality of the resulting 3D reconstruction. We use two approaches to analyze the 3D model fitting: comparing them to the orthophotomap and measuring the position among 3D reconstructions.